The Barriers and Facilitators Influencing Oral Health Behaviours of Families of Autistic Children: A Scoping Review - Amrit Chauhan; Helen Wilson; Peter Day; Kara Gray‐Burrows; Kathy Leadbitter; Sarah Baker; Zoe Mashman; Nicola Pickles; Karen Vinall‐Collier (Community Dentistry and Oral Epidemiology, 2026)
ABSTRACT Objectives To identify barriers and facilitators to home‐based oral health behaviours in families of autistic children, using the Theoretical Domains Framework (TDF) and Capability, Opportunity, Motivation–Behaviour (COM‐B) model. Methods A scoping review was conducted using Joanna Briggs Institute methodology and PRISMA‐ScR guidelines. Seven databases were searched up to March 2024. Eligible studies focused on parental views of oral health behaviours (toothbrushing and sugar reduction) for autistic children up to 18 years. Data were charted and mapped to the COM‐B model and the Theoretical Domains Framework (TDF). Results Seventeen studies were included across various countries including the USA, Hong Kong and Saudi Arabia. A total of 93 barriers and 81 facilitators were identified. Most identified influences related to the COM‐B ‘Opportunity’ domain. Key domains were ‘Environmental Context and Resources’, ‘Skills’, ‘Emotion’, ‘Social Influences’, and ‘Reinforcement’. Common barriers included sensory sensitivities, emotional strain, and skill challenges. Facilitators included environmental adaptations, support from professionals, and routine‐building. Dietary behaviours related to reducing sugary foods and drinks were rarely explored. Some behavioural domains (e.g., identity, optimism) were not represented. Conclusions This review provides a conceptually robust synthesis of modifiable behavioural influences on oral health in autistic children, grounded in parent/carer perspectives. It highlights critical gaps, especially the underrepresentation of sugar‐related dietary behaviours, alongside the need for adapted behavioural frameworks and greater evidence from diverse contexts beyond the USA. Findings contributed to the development of toothPASTE , a co‐designed intervention, and illustrate the broader potential of scoping reviews to bridge evidence and practice in developing inclusive, theory‐informed strategies for neurodivergent populations.